Model for Human Waist Size Estimation and the Recommended Pharmaceutical Tolerable Range for Humans (A Study of Federal University Wukari, Nigeria’s Campus Community) - D, Ogwumu O. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This research is concerned with the development of a mathematical model for estimating the Waist size of humans in relation with their height and weight. The model was validated in order to very whether it could estimate what it was created to measure by comparing the estimations of the model and the real-life sourced data from the study area. But, the outcome of the model's validation revealed that the model's data predictions are in strong agreement with the real life measurement with a correlation coefficient of 0.96796 and thus recommends the model as a standard model for estimating the waist size of humans.